RETRACTED : Peningkatan Teknik Shooting Melalui Model Pembelajaran Team Assisted Individualization (TAI) - Ishak, Muchamad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2017)
Following a rigorous, carefully concerns and considered review of the article published in jurnal SPORTIF to article entitled “Peningkatan Teknik Shooting Melalui Model Pembelajaran Team Assisted Individualization (TAI)” Vol 3, No 2, pp. 154-166, November 2017, DOI: https https://doi.org/10.29407/js_unpgri.v3i2.11891 The article contained redundant material, the editor investigated and found that the paper published in Jurnal Pedagogik Olahraga, Vol. 3, No. 1, pp. 1-14, Januari-Juni 2017. The document and its content has been removed from jurnal SPORTIF and reasonable effort should be made to remove all references to this article.